INCREASING PROCESS OF COMMUNITY PARTICIPATION IN RAWA GEDE COFFEE PRODUCT DESIGN, SIRNAJAYA TOURISM VILLAGE, SUKAMAKMUR DISTRICT - Yosi Erfinda; Rahmat Darmawan; Revi Agustin; Rinie Octavianny Hasan; Rifki Maulana; Najla Hanna; Shakira Yasmin Az Zahra (Universitas Airlangga, 2023)
Rawa Gede Agrotourism is a tourist attraction located in Sirnajaya Tourism Village, Sukamakmur District, Bogor Regency. Coffee is one of the largest plantation products in Sirnajaya Tourism Village. But so far the results of coffee plantations have not been used as typical souvenirs. The purpose of this community service activity is to provide skills in making coffee product packaging designs to coffee farmer groups, communities and tourism driving groups in rural areas. This series of activities starts from March to July 2023 and there are 2 (two) stages of community service that have been carried out including varied lectures presented by resource persons with some material that touched on tourism products and workshops in the form of direct training on making coffee product packaging designs. The success of this activity was evaluated using a krikpatrick evaluation model in the form of reaction evaluation and learning evaluation by providing a pre-test before the training began to measure participants' understanding of the material to be delivered then post-test was carried out after the workshop was completed. The results of this activity showed that the participants were very enthusiastic and motivated to promote Rawa Gede coffee products by expanding their target market through tourism activities in Sirnajaya Village and this activity could also improve the economy of rural communities.